Determination of 3-MeO-PCP in human blood and urine in a fatal intoxication case, with a specific focus on metabolites identification - Nadia Arbouche (Taylor & Francis Group, 2021)
3-Methoxyphencyclidine (3-MeO-PCP) is a new psychoactive substance that belongs to the phencyclidines family, first identified in Europe in 2012. This drug presents a stronger binding to N-methyl-D-aspartate (NMDA) receptors when compared to phencyclidine, which results in more potent effects, even at low concentrations. Very few articles have been published regarding 3-MeO-PCP in forensic toxicology. In this paper, the authors present a fatal 3-MeO-PCP intoxication case. In addition to the detection of the parent drug, metabolites were investigated in urine and, for the first time in the scientific literature, in blood. 3-MeO-PCP and its metabolites were quantitated by liquid chromatography-tandem mass spectrometry system (LC-MS/MS). Identification was confirmed by liquid chromatography-high resolution mass spectrometry (LC-HRMS). 3-MeO-PCP tested positive in femoral blood (3 525 ng/mL) and urine (7 384 ng/mL). The femoral blood concentration was higher than the fatal concentrations range already reported in the literature (from 50 to 3 200 ng/mL). 3-MeO-PCP metabolites, including O-demethyl-3-MeO-PCP, piperidine-OH-3-MeO-PCP, O-demethyl-piperidine-di-OH-3-MeO-PCP and piperidine-di-OH-3-MeO-PCP, were detected in blood. In addition, two new metabolites, O-demethyl-piperidine-OH-3-MeO-PCP and O-demethyl-cyclohexyl-OH, were identified in both blood and urine. Unfortunately, due to the lack of reference material on the market, it was not possible to measure the concentration of these metabolites. However, the ratios between the metabolites and the parent drug were useful to estimate their analytical response and prevalence. At this time, considering the low ratios (<1) between metabolites and parent drug, metabolites testing does not seem useful to increase the detection window of the drug.